Character education model based on islamic adab values in the tsanawiyah madrasah environment - Ade Tuti Komala; Ahmad Sukandar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research aims to develop a character education model, known as the A-K Model, based on Islamic adab values within the context of Madrasah Tsanawiyah in West Bandung Regency, utilizing a qualitative approach that employs the Research and Development (R&D) method. Data were collected through participatory observations, in-depth interviews with 15 teachers and 120 students, and Focus Group Discussions (FGD) involving Islamic education experts and madrasah practitioners. The study's findings revealed that integrating Islamic adab values into the four pillars integrated curriculum, teacher example, habituation of daily rituals (such as muhasabah), and community collaboration resulted in a 40% increase in student discipline and a 35% increase in empathy within one semester. This model introduces a multidimensional measurement index that combines quantitative (attendance, compliance) and qualitative (journal reflection, attitude observation) aspects, as well as community collaboration based on Bandura's Social Learning principles, Lickona's moral knowing–feeling–behavior concept, and Vygotsky's framework of social constructivism that emphasizes the role of social interaction in character formation in shaping social multiplication effects, in which 65% of parents report positive behavioral changes in the family environment. The conclusion of the study confirms that the A-K Model is not only effective in the socio-cultural context of West Bandung Regency but also answers the gap in previous literature by integrating the Islamic spiritual dimension into the framework of modern character education. Policy recommendations include case-based teacher training, dedicated budgeting for supporting facilities, and replication of models in regions with different characteristics.